2017
DOI: 10.1159/000480542
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria from Andean Grain Amaranth: A Source of Vitamins and Functional Value Enzymes

Abstract: Amaranth is a rediscovered pseudocereal with high nutritional properties. Lactic acid fermentation can increase the functional and nutritional value of foods. The aims of this study were to isolate and evaluate the functionality of lactic acid bacteria (LAB) from amaranth. LAB strains (n = 29) isolated from amaranth sourdough and grains included Lactobacillus (L.) plantarum (n = 8), L. rhamnosus (n = 6), Enterococcus (E.) mundtii (n = 4), E. hermanniensis (n = 3), E. durans (n = 1), Enterococcus sp. (n = 1), L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Intracellular and/or cell wall linked phytase activity was reported in L. brevis, L. curvatus, L. acidophilus [32] and L. fermentum [16]. Carrizo et al [23,24] reported that some LAB (Lactobacillus and Enterococcus strains) showed high phytase activity when grown in Chalmers broth [33] with sodium phytate 1% (w/v). On the basis of our results, L. plantarum CRL1964 was selected for further studies as it had a high phytase intracellular activity and growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intracellular and/or cell wall linked phytase activity was reported in L. brevis, L. curvatus, L. acidophilus [32] and L. fermentum [16]. Carrizo et al [23,24] reported that some LAB (Lactobacillus and Enterococcus strains) showed high phytase activity when grown in Chalmers broth [33] with sodium phytate 1% (w/v). On the basis of our results, L. plantarum CRL1964 was selected for further studies as it had a high phytase intracellular activity and growth.…”
Section: Discussionmentioning
confidence: 99%
“…LAB strains (n = 73, Table S1) isolated from grains and spontaneous sourdough of quinoa and amaranth [23,24], which belong to the Culture Collection of the Centro de Referencia para Lactobacilos (CRL; CERELA-CONICET), Tucumán, Argentina, were used in this study.…”
Section: Microorganisms and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are usually found in milk and dairy products but can be isolated from plant or animal sources-leaves, fruits, roots, faeces and compost [19]. They widely participate in cereal fermented products [6][7][8]17,18,22], as well as in spontaneously fermented amaranth, quinoa and chia sourdoughs [48][49][50][51][52].…”
Section: Lab Cereal Fermentation: Microbiology and Biochemistry Of Thmentioning
confidence: 99%
“…It has been shown that LAB can produce folates, riboflavina and even vitamin B12 and that this production is a straindependent trait [7]. Vitamin producing strains have been isolated from numerous ecological niches that include the human gastrointestinal tract, animal milks (including humans, dogs and horses), fermented foods (corn, potatoes, milks), flours and grains [8][9][10][11][12][13][14]. These vitamin-producing strains have traditionally been used for the development of novel biofortified foods that could be used as an alternative to fortification with chemically synthesized or purified derivatives of vitamins.…”
Section: Vitamin-producing Labmentioning
confidence: 99%